Direct numerical simulation of droplet deformation in turbulent flows with different velocity profiles. (1st July 2019) - Jiao, Daokuan; Jiao, Kui; Zhang, Fan; Du, Qing
Highlights: Droplet deformation rates are complicated in uniform/turbulent velocity fields. Deformation processes closely relate to velocity profiles. Droplets tend to be turned up and down with Half integral scale profiles. Droplets tend to be turned and rotated with Quarter integral scale profiles. Droplets tend to be squeezed sideways with Tenth integral scale profiles. Abstract: The deformation and fragmentation processes of single droplet in turbulent velocity flows are compared with the continuous uniform velocity inlet profile flows. Direct numerical simulation (DNS) coupled with volume of fluids (VOF) method is adopted to solve the flow equations and track the liquid–gas interfaces. By varying the turbulence integral length scales, different inlet velocity profiles are generated. Meanwhile, the inlet velocity magnitude changes in a wide range to present the turbulence and Weber number effects on droplet deformation. The temporal and spatial evolution processes of the droplet are taken into consideration. After analyzing the velocity distribution, the motion of the turbulent flow fronts and the scales of the turbulent vortices, the deformation differences between the uniform and turbulent fields are clearly explained. Different from uniform velocity profile, droplet shows an unsteady and unsymmetrical deformation in the turbulence fields. In the later stage, the droplet breakup in the turbulent fields is more intensive and thorough. Due to the velocity fluctuations, the pressure around the droplet is abruptly distributed which causes the droplet to be turned, rotated and side-squeezed. The droplets tend to be turned up and down with the Half integral scale profiles, be turned and rotated with the Quarter while be squeezed sideways with the Tenth. This asymmetrical deformation tendency may stimulate or counteract the transport process. This will help improve the comprehension of the droplet breakup in internal combustion engines and other industrial activities.